A Phase 2 study of L‐asparaginase encapsulated in erythrocytes in elderly patients with Philadelphia chromosome negative acute lymphoblastic leukemia: The GRASPALL/GRAALL‐SA2‐2008 study. Issue 9 (September 2015) - Hunault‐Berger, Mathilde; Leguay, Thibaut; Huguet, Françoise; Leprêtre, Stéphane; Deconinck, Eric; Ojeda-Uribe, Mario; Bonmati, Caroline; Escoffre‐Barbe, Martine; Bories, Pierre; Himberlin, Chantal; Chevallier, Patrice; Rousselot, Philippe; et al.
<x xml:space="preserve">Abstract</x> Purpose: The GRASPALL/GRAALL‐SA2‐2008 Phase II trial evaluated the safety and efficacy of L‐asparaginase encapsulated within erythrocytes (GRASPA®) in patients ≥ 55 years with Philadelphia chromosome‐negative acute lymphoblastic leukemia. Findings: Thirty patients received escalating doses of GRASPA® on Day 3 and 6 of induction Phases 1 and 2. The primary efficacy endpoint was asparagine depletion < 2 µmol/L for at least 7 days. This was reached in 85 and 71% of patients with 100 and 150 IU/kg respectively but not with 50 IU/kg. Grade 3/4 infection, hypertransaminasemia, hyperbilirubinemia and deep vein thrombosis occurred in 77, 20, 7, and 7% of patients, respectively. No allergic reaction or clinical pancreatitis was observed despite 17% of Grade 3/4 lipase elevation. Anti‐asparaginase antibodies were detected in 50% of patients and related to a reduction in the duration of asparagine depletion during induction Phase 2 without decrease of encapsulated L‐asparaginase activity. Complete remission rate was 70%. With a median follow‐up of 42 months, median overall survival was 15.8 and 9.7 months, in the 100 and 150 IU/kg cohorts respectively. Conclusions: The addition of GRASPA®, especially at the 100 IU/kg dose level, is feasible in elderly patients without excessive toxicity and associated with durable asparagine depletion. (clinicaltrials.gov identifier NCT01523782). Am. J. Hematol. 90:811–818, 2015. © 2015 Wiley Periodicals, Inc.